ENGLISH FOLKLORE AS A MEANS OF SOCIOCULTURAL COMPETENCE DEVELOPMENT - Natalia Bachynska (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article deals with the problem of sociocultural competence development of students majoring in 'Musical Art' by means of English folklore. The notions 'sociocultural competence' and 'folklore' have been revealed. The use of English folk songs in the process of development of sociocultural competence of students majoring in 'Musical Art' has been grounded; the classification of English folk songs has been provided. The system of exercises which helps develop sociocultural competence have been given. The exercises have been divided into three groups. The exercises for setting students' mind on the subject of the lesson and acquaintance with the genres of English poetic folklore, acquaintance with lexical units with a national and cultural component and understanding of sociocultural information extracted from English poetic folklore belong to the first group. The exercises on comparison of English poetic folklore forms with corresponding forms in Ukrainian language and recreation of sociocultural information have been referred to the second group. The exercises on activation and fixing of sociocultural material belong to the third group. The examples of exercises have been given to each group.